Prototype of Monitoring and Alarm for the Detection of White Frosts in Rural Sectors of Sogamoso - Salamanca-Figueroa, Fabián Andrés; Suarez-Rodrígez, Willmar Arbey; Cárdenas-Gamboa, Christian Camilo (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2018)
The next article shows of prototype of monitoring and alarm that it allows for the detection of white frost, which is the base to develop a prototype for detention and predictions of other types of frost. The device shows the atmospheric variables of temperature and humidity, this data is sent to a local server broker with Wifi protocol MQTT. This one retransmit the info to end devices like cellphones and laptops. The system is capable of alerting with an alarm and it allows for the events communication to different end devices. To do this was necessary to select the appropriate devices, technologies and protocols, design and validate them, emulating the appropriate temperature and humidity conditions.